Pemenuhan dan Perlindungan Hak Anak terhadap Perkawinan Anak oleh Masyarakat Adat - Sitohang, Yesica Yentelina; Hardinata, Michelle Jefelyn; Anjelina, Fatrecya Mutiara; Subroto, Aryo (Syntax Corporation, 2025)
Child marriage remains a prevalent issue in various regions of Indonesia, particularly within indigenous communities. Despite government efforts to prohibit and restrict this practice through legislation, traditional norms often hold greater influence over the age of marriage. This study aims to examine the impact of child marriage on children's rights within indigenous communities in Indonesia and evaluate the effectiveness of existing legal protections for these children. The research employs a case study methodology with a normative legal approach, focusing on the analysis of written sources such as legislation, legal principles, legal theories, and relevant literature. The study finds that child marriage adversely affects various aspects of a child's life, including education and health. Furthermore, although there are laws designed to protect children's rights, their implementation remains weak within indigenous communities.